In‐situ formation of Zn–Al layered double oxides on electrochemically anodized nanoporous aluminum film as sorbent for chlorophenols extraction from water and wastewater followed by determination using HPLC. Issue 6 (21st January 2021) - Ghani, Milad; Raoof, Jahan Bakhsh; Masoum, Saeed
Abstract: Herein, we present a simple, cost‐effective, and robust strategy for the in‐situ preparation of Zn‐Al layered double oxides–anodized aluminum thin film via a facile hydrothermal method, followed by calcination treatment of the Zn‐Al layered double hydroxide in the air atmosphere. The in‐situ prepared Zn‐Al layered double oxide‐anodized aluminum film was implemented as sorbent for thin film microextraction of four selected chlorophenols (4‐chlorophenol, 2, 4‐dichlorophenol, 2, 4, 6‐trichlorophenol, and pentachlorophenol), followed by high‐performance liquid chromatography‐ultraviolet detection. The different variables of the thin film microextraction were screened via Plackett–Burman design and then optimized through Box–Behnken design. Under the optimum condition, the method showed good linear ranges (0.2‐200 μg/L) with the coefficient of determinations higher than 0.9938. The calculated limit of detections were between 0.07 and 0.56 μg/L. Relative standard deviations of the method for determination of the analytes at 5 μg/L concentration level (n = 3) were ranged from 3.5 to 3.9% (as interday). The enrichment factors were between 39 and 58. This extraction method was demonstrated to be fast, efficient, and convenient. To study the capability of the developed method for real sample analysis, tap, well, river, and two types of wastewater samples were satisfactorily analyzed.